AB1019 Is The Self-Assessment of Disease Activity (auto-DAS28) by Patients A Feasible and Acceptable Measure over The Long Term in Rheumatoid Arthritis (RA)? Three-Year Follow-up of A Nurse-Led Program in 771 Patients with Established RA. (15th July 2016) - Gossec, L.; Molto, A.; Foissac, F.; Soubrier, M.; Fayet, F.; Gaudin, P.; Dougados, M.
Abstract : Background: Patients with RA can be trained in self-assessment of disease activity by a self-assessment of their joints and calculation of the Disease activity Score 28 (DAS28) [1]. Objectives: To assess if such an auto-DAS assessment is a feasible measure over the long-term (i.e., do patients adhere to such an assessment) and to determine the characteristics of patients related to adherence to auto-DAS. Methods: This was an open long term (2–4 years) extension of the 6 month randomized controlled COMEDRA trial of patients with definite, stable RA. Patients were trained to perform auto-DAS by a nurse, using a video and teaching of self-assessment of joints (the training took approximately 30 minutes) and nurses provided the advice to perform the auto-DAS regularly in a dedicated booklet. 2–4 years after the end of the trial, patients were seen in a face-to-face interview with a nurse and the frequency of auto-DAS was assessed through the auto-DAS booklet and if unavailable, from patient questioning. Adherence to auto-DAS was defined as the performance of at least one auto-DAS more than 6 months after the end of the trial. Characteristics of adherent versus non adherent patients were compared by univariate and multivariate logistic regression analyses and included demographic and disease activity variables as well as the centre (high versus low inclusion rate, based on the median). Results: Of the 970 recruited patients, 771 (79.5%) were followed up at 3 years and had available data regarding auto-DAS: mean (±standard deviation) age 61 (±11) years, median [IQR] disease duration 15 [9 - 23] years; 615 (80%) were women and 82% had received a biologic. The mean (±sd) baseline and 3-year DAS28 scores were respectively 3.1±1.3 and 2.8±1.4. After 3 years, 354 (46%) patients were adherent to auto-DAS (i.e., had at least one auto-DAS completed more than 6 months after the end of the trial). For adherent patients the median [IQR] number of auto-DAS performed was 5.4 [1.7 – 12.8] overall, i.e. 2.3 [0.8 – 5.9] per year. However among the adherent population, the number of patients who completed their autoDAS booklet at least once per year decreased over time, with 351 (99%), 162 (46%) and 118 (33%) patients respectively for 2012, 2013 and 2014 (p<0.0001). In the multivariate analysis, only larger inclusion centres were significantly associated to an adherent behaviour (OR [95% CI] 2.9 [2.0 – 4.1], p<0.0001). Conclusions: After a short training, many of these long-standing, moderately active RA patients continued to perform an auto-DAS, though the performance of auto-DAS decreased over time in this cohort where patients did not receive any ongoing positive feedback on their auto-DAS. In the larger inclusions centres, autoDAS adherence was higher, perhaps related to more patient/physician interaction around autoDAS results. Self-assessment of disease activity is feasible in RA but positive reinforcement appears necessary. Further studies should analyse if outcomes are better for patients who self-assess. References: Dougados M, Soubrier M, et al. Ann Rheum Dis. 2015;74(9):1725–33. Acknowledgement: grant from the French National Research Program (PHRC AOM 12072). Disclosure of Interest: None declared